Method for rapidly preparing super-hydrophobic silicon dioxide aerogel monolith through normal-pressure drying and solvent-free replacement
Through the method of solvent-free replacement of atmospheric pressure drying, the complexation of quaternary ammonium base and silicate ions is used to gel at a certain pH, which solves the risk of high-pressure drying and the time-consuming and material consumption of solvent replacement in the existing silica aerogel preparation method, and achieves the rapid and safe preparation of superhydrophobic silica aerogel monolith, with excellent performance and wide application prospects.
Patent Information
- Application Number
- CN202510181194.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-25
AI Technical Summary
The existing preparation methods for silica aerogels have the problems of high-pressure drying and the time-consuming and material consumption of solvent replacement, which limit the promotion and application of materials.
The solvent-free replacement method is used to dry at normal pressure, and gelatinize the quaternary ammonium base and silicate ions at a certain pH through the complexation of the quaternary ammonium base and silicate ions to form a regular fibrous structure, and is treated in acidic and hydrophobic modifiers, and finally dried at normal pressure.
It realizes the rapid and safe preparation of superhydrophobic silica aerogel monoliths, with high specific surface area, low density, low thermal conductivity and superhydrophobicity, and is suitable for a variety of application fields.
Smart Images

Figure CN119873839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to a method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free replacement. Background Art
[0002] Aerogel has many remarkable properties, including extremely high porosity, high specific surface area, low density, ultra-low dielectric constant and low thermal conductivity. It is considered to be the third generation of insulating materials and one of the best insulating materials invented so far. Silica aerogel can be widely used in adsorbents, thermal insulation materials, catalysts, sensors and media, and has great market potential.
[0003] Although silica aerogel has excellent performance, there are still certain deficiencies in the preparation method, which limits the promotion and application of silica aerogel materials. The preparation of silica aerogel mostly adopts supercritical drying technology. For example, the Chinese invention patent with publication number CN101863479A provides a method for preparing silica aerogel by supercritical drying with a high-pressure liquid medium, comprising the following steps: (1) under acidic conditions of pH=3~5, adding silicon tetrachloride and water to stir the reaction, then adjusting the pH=8~10 with ammonia water, and then adding water and ethanol to perform hydrolysis-condensation reaction to form alcohol gel; (2) loading the alcoholized gel into a high-pressure reactor, filling the reactor with high-pressure liquid medium, and slowly heating the reactor until the supercritical pressure is reached; (3) then slowly heating and slowly releasing the medium gas until the pressure in the reactor is balanced with the external atmospheric pressure, opening the reactor, taking out the sample, and drying. This type of process can maintain the integrity of the gel structure and avoid structural collapse caused by capillary force. However, the drying process is carried out under a certain pressure, which is dangerous and difficult to use on a large scale. In addition, freeze-drying technology uses the solidification and sublimation of solvents in wet gels to avoid the influence of capillary stress, but when the solvent changes from liquid to solid, it may cause certain damage to the structure of the aerogel and is not applicable to some materials. Both of the above methods require multiple solvent replacements, which consume organic reagents and time.
[0004] The Chinese invention patent with publication number CN111232990A discloses a method for efficiently preparing silica aerogel by solvent vapor exchange, which includes the following preparation process: (1) removing Na from the mixed solution of water glass hydrolysis by a strong acid cation exchange resin; +, obtain silicic acid, and then add trimethylchlorosilane and ammonia water to obtain a wet gel; (2) age the wet gel, and then soak it in a modifying liquid to obtain a modified wet gel; (3) use acetone / n-hexane vapor to perform solvent exchange on the modified wet gel to obtain a solvent-exchanged wet gel; (4) dry the solvent-exchanged wet gel at normal pressure to obtain a hydrophobic silica aerogel. Compared with direct n-hexane solvent exchange, the method of the invention has a faster solvent exchange efficiency and uses less solvent, thus avoiding the problems of long solvent exchange cycle and large solvent waste, and can maintain the complete silica aerogel structure. The technical conditions for normal pressure drying are relatively simple, but it usually requires surface modification of the gel, and solvent replacement is also inevitable, otherwise the gel is prone to breakage. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement is provided, which has a convenient process, and comprises the following steps: (1) Mix silicon dioxide, quaternary ammonium alkali and water and heat until silicon dioxide is completely dissolved to obtain a quaternary ammonium alkali silicate solution WG[(R 4 N) + ]; (2) Add alcohol and silicate to the quaternary ammonium alkali silicate solution WG[(R 4 N) + ] and mixed to obtain a sol; (3) adding a strong acid solution to the sol to form a gel; (4) The gel is aged and then immersed in an acidic solution at a certain temperature until the gel becomes acidic, thereby obtaining an acidic wet gel; (5) Soaking the acidic wet gel in a hydrophobic modifier at a certain temperature for modification to obtain a modified wet gel; (6) The modified wet gel is dried under normal pressure to obtain a superhydrophobic silica aerogel monolith.
[0006] Preferably, in step (1), the quaternary ammonium base includes at least one of tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), and tetrapropylammonium hydroxide (TPAOH).
[0007] Preferably, in step (1), the mass ratio of quaternary ammonium hydroxide, water and silicon dioxide is 1~1.5:2.5~4:1.25~2.
[0008] During the preparation, too low a silicon dioxide content can easily lead to the breakage of the aerogel. The amounts of quaternary ammonium base, water and silicon dioxide should be controlled within the preferred ratio range of the present invention.
[0009] Preferably, in step (1), the heating reaction temperature is 60-100°C and the time is 6-20 h.
[0010] Preferably, in step (2), the alcohol comprises at least one of methanol, ethanol, isopropanol and n-propanol; and the amount of alcohol added is ≥50% by volume of the entire gel when the gel is formed.
[0011] When the amount of alcohol added is lower than the preferred range, it will affect the structure of the aerogel and the hydrophobic modification effect, so its addition amount is preferably controlled to be ≥50%.
[0012] Preferably, in step (2), the silicate comprises at least one of tetramethylorthosilicate (TMOS), tetraethylorthosilicate (TEOS), tetrapropylorthosilicate (TPOS), and polysilicate; the silicate and the quaternary ammonium alkali silicate solution WG[(R 4 N) + ]The molar ratio of silicon atoms provided is 0~0.4:1.
[0013] Silicates can replace WG[(R 4 N) + ] As a silicon source, within the preferred range of the present invention, the technical problem in the art can add an appropriate amount of silicate or not add silicate according to actual needs, but it should not exceed the above range. If the added amount is greater than this range, the aerogel is prone to breakage.
[0014] Preferably, in step (2), the mixing temperature is 0-25°C and the mixing time is 10-30 min.
[0015] Preferably, in step (3), the solvent of the strong acid solution includes at least one of alcohol and water, and the strong acid includes at least one of sulfuric acid, hydrochloric acid and nitric acid; and the pH of the gel is 8-10.
[0016] Preferably, in step (4), the gel is allowed to stand for 0 to 2 hours and then immersed in an acidic solution, and kept warm at 45 to 70° C. until the gel becomes acidic, thereby obtaining an acidic wet gel.
[0017] Preferably, in step (4), the solvent of the acidic solution comprises at least one of alcohol and water, wherein the acid comprises at least one of phosphoric acid, citric acid, acetic acid, oxalic acid, sulfuric acid, hydrochloric acid and nitric acid; and the amount of the acidic solution added is 1 to 2 times the volume of the gel.
[0018] Preferably, in step (5), the acidic wet gel is immersed in a hydrophobic modifier and subjected to a modification treatment at a temperature of 45-65° C. until the acidic solution in the acidic wet gel is completely discharged.
[0019] Preferably, in step (5), the hydrophobic modifier comprises one of hexamethyldisiloxane and hexamethyldisilazane; and the amount of the hydrophobic modifier added is 1 to 2 times the volume of the acidic wet gel.
[0020] Preferably, in step (6), the drying temperature is 60-240° C. and the drying time is 1-6 h.
[0021] In the second aspect of the present invention, a super-hydrophobic silica aerogel monolith with low thermal conductivity, low density, high specific surface area and porosity is provided, which is prepared by the method provided by the first aspect of the present invention.
[0022] Preferably, the specific surface area of the super hydrophobic silica aerogel monolith is 600-850 m 2 / g.
[0023] Based on the above technical solutions, the design concept and principle of the present invention are as follows: The present invention is designed to utilize the electrostatic attraction and complexation of quaternary ammonium cations and silicate ions to form a relatively stable and complex complex structure. Gelation at a certain pH can enhance the skeleton structure of the aerogel and form a regular fibrous structure. In the preferred range, the WG[(R 4 N) + ] and alcohol are added in a proportion that is conducive to strengthening the structure of silica gel and improving the stability of the skeleton structure of silica aerogel. By hydrophobic modification of the gel, the destructive effect of capillary stress on the aerogel structure is reduced. Finally, it is dried at normal pressure to obtain a complete super-hydrophobic silica aerogel monolith. The silicon source of the present invention is widely available, and natural or synthetic silica can be used as the silicon source, and silicate can be used selectively. Silica aerogel is prepared at normal pressure, with a short preparation time, without the need for low surface tension solvent replacement, and the obtained aerogel is not easy to break when dried. At the same time, it has low thermal conductivity, low density, high specific surface area and porosity, and is super-hydrophobic.
[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for rapidly preparing a super-hydrophobic silica aerogel monolith by drying at normal pressure without solvent replacement. The method has the advantages of preparation at normal pressure, short production time, and no need for solvent replacement. The product is not easy to break during drying, and the preparation of the super-hydrophobic silica aerogel monolith is achieved with high efficiency.
[0025] The invention provides a super-hydrophobic silica aerogel monolith, which has super-hydrophobicity, high specific surface area and porosity, low thermal conductivity and low density, and has good application prospects in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an electron microscope image of the super hydrophobic silica aerogel monolith prepared in Example 1; Figure 2 This is an infrared spectrum of the super hydrophobic silica aerogel monolith prepared in Example 1; Figure 3 This is a water contact angle test diagram of the super hydrophobic silica aerogel monolith prepared in Example 1; Figure 4 This is a physical picture of the super hydrophobic silica aerogel monolith prepared in Example 1; Figure 5 This is an electron microscope image of the superhydrophobic silica aerogel monolith prepared in Example 2. DETAILED DESCRIPTION
[0027] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0028] Example 1 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TPAOH, water and silica were mixed in a ratio of 8:12:5, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TPA + )],spare; (2) WG[(TPA + )] and ethanol in a mass ratio of 1:0.7 were mixed and stirred for 10 min to obtain a sol; (3) adding 10 wt.% sulfuric acid in alcohol (80 wt.% ethanol) to the sol to gelate it to form a gel, the pH of the gel being 8.5; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid aqueous solution and kept at 60 °C for 2 h to obtain an acidic wet gel; (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 150 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0029] The microstructure of the super hydrophobic silica aerogel prepared in this example was observed by scanning electron microscopy. Figure 1 As shown in the figure, the skeleton structure of the superhydrophobic silica aerogel monolith is thick and not broken.
[0030] The superhydrophobic silica aerogel monolith was characterized by infrared spectroscopy. Figure 2 As shown in the figure, at 1048 cm -1 、757 cm -1 and 425 cm -1 The strong and broad absorption peak at 2960 cm-1 can be attributed to the symmetric and asymmetric stretching vibration and bending vibration of Si-O-Si bonds, indicating that the aerogel has Si-O-Si as its basic skeleton structure. -1 , 1255 cm -1 and 843 cm -1 The narrow and sharp absorption peak at 3 Antisymmetric stretching vibration, bending vibration and symmetric stretching vibration of the bond, CH 3 The groups are the chemical basis of the hydrophobicity of aerogels.
[0031] The hydrophobic properties of the superhydrophobic silica aerogel monolith were tested using a contact angle tester (KRUSS DSA100S) (2 μL water droplet). Figure 3 As shown in the figure, its water contact angle is 166°, which is super hydrophobic.
[0032] The actual photo of super hydrophobic silica aerogel monolith is shown in Figure 4 As shown. The white product in the figure is the prepared super-hydrophobic silica aerogel monolith, which has a uniform and stable structure and no breakage, indicating that the target material has been successfully prepared by this method. In the figure, the aerogel floats above the water, and the blue water droplets above the aerogel are spherical, reflecting the good super-hydrophobicity of the aerogel material.
[0033] In addition, the density of the superhydrophobic silica aerogel monolith was calculated to be 0.11 g / cm by mass-to-volume ratio. 3 The specific surface area of the material was 758.64 m 2 / g; the thermal conductivity was tested by a Swedish thermal conductivity meter (Hot Disk TPS 2500S) with reference to standard ISO 22007-2 and was 0.044 W / m·K. The above results show that the superhydrophobic silica aerogel monolith has low thermal conductivity, low density, high specific surface area and porosity, and is superhydrophobic.
[0034] Example 2 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TPAOH, water and silica were mixed in a ratio of 8:12:5, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TPA + )],spare; (2) WG[(TPA + )] and ethanol were mixed in a mass ratio of 1:1.4 for 10 min, and then TEOS, WG[(TPA + )] and TEOS silicon source in a ratio of 2:1, stirred for 20 min to obtain a sol; (3) adding 10 wt.% sulfuric acid aqueous solution to the sol to gelate it to form a gel, the pH of the gel being 8.5; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid aqueous solution and kept at 60 °C for 2 h to obtain an acidic wet gel; (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 120 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0035] The scanning electron microscope image of the super hydrophobic silica aerogel monolith of this example is as follows Figure 5 The results show that its skeleton structure is thick and not broken. The density is 0.11 g / cm 3 , with a specific surface area of 687.75 m 2 / g, thermal conductivity 0.042 W / m·K, water contact angle 164°, and superhydrophobicity.
[0036] Example 3 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TMAOH, water and silica were mixed in a ratio of 19:56:25, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TMA + )],spare; (2) WG[(TMA + )], isopropanol were mixed in a mass ratio of 1:1.8 for 10 min, and then TEOS, WG[(TMA + )] and TEOS silicon source in a ratio of 4:1, stirred for 20 min to obtain a sol; (3) adding 10 wt.% sulfuric acid aqueous solution to the sol to gelate it to form a gel, the pH of the gel being 8.5; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid aqueous solution and kept at 60 °C for 2 h to obtain an acidic wet gel. (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 150 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0037] After testing, the density of the super hydrophobic silica aerogel monolith of this embodiment is 0.11 g / cm 3 , with a specific surface area of 721.25 m 2 / g, thermal conductivity 0.039 W / m·K, water contact angle 162°, and superhydrophobicity.
[0038] Example 4 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TEAOH, water and silica were mixed in a ratio of 17:22:11, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TEA + )],spare; (2) WG[(TEA + )] and methanol were mixed in a mass ratio of 1:0.1 and stirred for 10 min, and then TMOS, WG[(TEA + )] and TMOS silicon source in a ratio of 3:1, stirred for 20 min to obtain a sol; (3) adding 10 wt.% sulfuric acid in alcohol (80 wt.% ethanol) to the sol to gelate it to form a gel, the pH of the gel being 8.5; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid in alcohol (50 wt.% ethanol) and kept at 60 °C for 2 h to obtain an acidic wet gel. (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 150 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0039] After testing, the density of the super hydrophobic silica aerogel monolith of this embodiment is 0.11 g / cm 3 , with a specific surface area of 751.35 m 2 / g, thermal conductivity 0.043 W / m·K, water contact angle 159°, and superhydrophobicity.
[0040] Example 5 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TPAOH, water and silica were mixed in a ratio of 8:12:5, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TPA + )],spare; (2) WG[(TPA + )] and ethanol were mixed in a mass ratio of 1:1.4 for 10 min, and then TEOS, WG[(TPA + )] and TEOS silicon source in a ratio of 2:1, stirred for 20 min to obtain a sol; (3) adding 10 wt.% sulfuric acid aqueous solution to the sol to gelate it to form a gel, and the pH of the gel was 9.0; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid aqueous solution and kept at 60 °C for 2 h to obtain an acidic wet gel; (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisilazane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 120 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0041] After testing, the density of the super hydrophobic silica aerogel monolith of this embodiment is 0.11 g / cm 3 , with a specific surface area of 631.31 m 2 / g, thermal conductivity 0.044 W / m·K, water contact angle 160°, and superhydrophobicity.
[0042] Example 6 A method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement, comprising the following steps: (1) TPAOH, water and silica were mixed in a ratio of 8:12:5, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TPA + )],spare; (2) WG[(TPA + )] and ethanol in a mass ratio of 1:0.7 were mixed and stirred for 10 min to obtain a sol; (3) adding 10 wt.% hydrochloric acid in alcohol (80 wt.% ethanol) to the sol to gelate it to form a gel, the pH of the gel being 8.5; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% acetic acid aqueous solution and kept at 60 °C for 4 h to obtain an acidic wet gel; (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 120 °C under normal pressure for 2 h to obtain a superhydrophobic silica aerogel monolith.
[0043] After testing, the density of the super hydrophobic silica aerogel monolith of this embodiment is 0.11 g / cm 3 , with a specific surface area of 683.35 m 2 / g, thermal conductivity 0.044 W / m·K, water contact angle 158°, and superhydrophobicity.
[0044] Comparative Example 1 A method for rapidly preparing super-hydrophobic silica aerogel by normal pressure drying and solvent-free displacement, the steps are as follows: (1) TPAOH, water and silica were mixed in a ratio of 8:12:5, heated and stirred at 90 °C until the silica was completely dissolved to obtain WG[(TPA + )],spare; (2) WG[(TPA + )] and ethanol in a mass ratio of 1:0.7 were mixed and stirred for 10 min to obtain a sol; (3) adding 10 wt.% hydrochloric acid in alcohol (80 wt.% ethanol) to the sol to gelate it to form a gel, the pH of the gel being 6; (4) After the gel was allowed to stand for 2 h, it was immersed in an equal volume of 20 wt.% sulfuric acid aqueous solution and kept at 60 °C for 4 h to obtain an acidic wet gel; (5) Soaking the acidic wet gel in 2 volumes of hexamethyldisiloxane and keeping it at 60 °C for 4 h to obtain a modified wet gel; (6) The modified wet gel was dried at 120 °C for 2 h under normal pressure to obtain superhydrophobic silica aerogel crumbs, but no whole material was obtained.
[0045] In summary, the present invention is to mix silicon dioxide powder, quaternary ammonium alkali and water to obtain a quaternary ammonium alkali silicate solution WG[(R 4 N) +] is the main silicon source, and the gelation at a certain pH value can strengthen the skeleton structure of the gel through the complexation of quaternary ammonium ions on silicate ions. The gel does not need to be aged for a long time, and does not need to be replaced multiple times with low surface tension solvents. The preparation process is short in time, and the drying temperature requirement is not high. The obtained aerogel is not easy to break when dried. The prepared silica aerogel monolith has excellent properties such as high specific surface area, low density, low thermal conductivity and super hydrophobicity, and has good application prospects in the corresponding fields.
[0046] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for rapidly preparing a super-hydrophobic silica aerogel monolith by drying at normal pressure and solvent-free displacement, characterized in that: The steps include: (1) Mix silicon dioxide, quaternary ammonium alkali and water and heat until silicon dioxide is completely dissolved to obtain quaternary ammonium alkali silicate solution WG[(R4N) + ]; (2) Add alcohol and silicate to the quaternary ammonium alkali silicate solution WG[(R4N) + ] and mixed to obtain a sol; (3) adding a strong acid solution to the sol to form a gel; (4) The gel is aged and then immersed in an acidic solution at a certain temperature until the gel becomes acidic, thereby obtaining an acidic wet gel; (5) Soaking the acidic wet gel in a hydrophobic modifier at a certain temperature for modification to obtain a modified wet gel; (6) The modified wet gel is dried under normal pressure to obtain a superhydrophobic silica aerogel monolith.
2. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by solvent-free displacement at normal pressure drying according to claim 1, characterized in that: In the step (1), the quaternary ammonium base includes at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide; and the mass ratio of the quaternary ammonium base, water and silicon dioxide is 1~1.5:2.5~4:1.25~2.
3. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (1), the heating reaction temperature is 60-100°C and the time is 6-20 hours.
4. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: The alcohol includes at least one of methanol, ethanol, isopropanol and n-propanol; the alcohol addition amount is ≥50% based on the percentage of alcohol addition amount to the whole gel volume when forming gel; the silicate includes at least one of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate and polysilicate; the silicate and quaternary ammonium alkali silicate solution WG[(R4N) + ]The molar ratio of silicon atoms provided is 0~0.4:
1.
5. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (2), the mixing temperature is 0-25°C and the mixing time is 10-30 min.
6. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (3), the solvent of the strong acid solution includes at least one of alcohol and water, and the strong acid includes at least one of sulfuric acid, hydrochloric acid, and nitric acid; and the pH of the gel is 8-10.
7. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (4), the gel is allowed to stand for 0 to 2 hours and then immersed in an acidic solution, which is kept warm at 45 to 70°C until the gel becomes acidic, thereby obtaining an acidic wet gel; the solvent of the acidic solution includes at least one of alcohol and water, wherein the acid includes at least one of phosphoric acid, citric acid, acetic acid, oxalic acid, sulfuric acid, hydrochloric acid, and nitric acid; and the amount of the acidic solution added is 1 to 2 times the volume of the gel.
8. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (5), the acidic wet gel is immersed in a hydrophobic modifier and subjected to a modification treatment at a temperature of 45 to 65° C. until the acidic solution in the acidic wet gel is completely discharged; the hydrophobic modifier comprises one of hexamethyldisiloxane and hexamethyldisilazane; and the amount of the hydrophobic modifier added is 1 to 2 times the volume of the acidic wet gel.
9. The method for rapidly preparing a super-hydrophobic silica aerogel monolith by normal pressure drying and solvent-free displacement according to claim 1, characterized in that: In the step (6), the drying temperature is 60-240°C and the drying time is 1-6 hours.
10. A super-hydrophobic silica aerogel monolith, characterized in that: The method is as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing silica aerogel by supercritical drying with high-pressure liquid medium
CN101863479A
Method for efficiently preparing silicon dioxide aerogel by solvent steam exchange method[v]
CN111232990A